Debt in Industry Equilibrium - Fries, Steven; Miller, Marcus; Perraudin, Wlliam (Review of Financial Studies, 1997)
This article shows (1) how entry and exit of firms in a competitive industry affect the valuation of securities and optimal capital structure, and (2) how, given a trade-off between tax advantages and agency costs, a firm will optimally adjust its leverage level after it is set up. We derive simple pricing expressions for corporate debt in which the price elasticity of demand for industry output plays a crucial role. When a firm optimally adjusts its leverage over time, we show that total firm value comprises the value of discounted cash flows assuming fixed capital structure, plus a continuum of options for marginal increases in debt.